The Cooperatives Performance Indicators, Based on Balance Scorecard - Surjaatmadja, Surachman (2020)
The Objectives Measurement of Cooperation Performance Indicators of Balance Score Card-Based (BSC) is to know the performance of certified cooperatives in Jakarta (capitol of Indonesia). Specific targets to be generated from this research are the Measurement of Cooperative Performance Indicators that can measure the performance of the Cooperative at the moment and can be used as a consideration for future decision making in a sustainable manner.  The research methodology used is descriptive, beginning with identifying and describing various aspects of cooperatives related to cooperative performance from a business side, such as marketing, operation/production, finance, human resources, legality, institutional, cooperation and so on. This research was carried out through a survey in several certified cooperatives in Jakarta that was sampled. The data were collected by using questionnaires, interviews and observation and in-depth interviews. The results of this study indicate in general from every perspective of Balance Score Card that from the perspective of the financial, certified cooperative in Jakarta, has average size of 3.223, on a scale of 1-5, while from Marketing perspective: 1.912, from the perspective of Internal Business Process: 1.765, and from a Growth and Learning perspective of: 2,370.